Comparison of the efficacy and safety of isepamicin plus metronidazole and amikacin plus metronidazole in intra-abdominal infections (Medical Journal of Indonesia, 2001)
Intra-abdominal infections due to penetrating wound through the abdominal wall or rupture of the gastrointestinal tract are acute conditions requiring prompt surgical intervention and the use of appropriate antimicrobial agents. Isepamicin is an effective aminoglycoside against various Gram-negative pathogens causing intra-abdominal infections. The objective of the present study is to compare the efficacy and safety of isepamicin (15 mg/kgBW IV o.d.) with amikacin (7.5 mg/kgBB b.i.d.), in conjunction with metronidazole for both drugs. An open, randomized, parallel design was applied in this trial. The subject allocation ratio for isepamicin: amikacin is 2:1. Out of 50 patients enrolled in this study, 27 fuffilled the criteria for safety and efficacy population, and 46 for intent-to-treat population. In the safety and efficacy population, the clinical success rare for isepamicin and amikacin group did not differ significantly (i.e., 95% and 100%, respectively). In the intent-to-treat population, the clinical success rates for isepamicin and amikacin group were also insignifficantly different (i.e., 97% and 100%, respectively). The rates of bacteriological elimination for isepamicin and amikacin, were 95% and 100%, respectively in the efficacy and safety population, and 90% and 93%, respectively in the intent-to-treat population. Streptococci and staphylococci were the most frequent (40%) pathogens isolated from pus, and Acinetobacter anitratus (55%) was the most common one isolated from blood. In the efficacy and safety population, the mean (± SD) length of hospital stay in the isepamicin and amikacin groups was 10.7 ± 3.9 and 11.1 ± 3.8 days, respectively, while in the intent-to-treat population, the mean (± SD) length of hospital stay in the isepamicin and amikacin groups was 10.1 ± 3.4 and 10.5 ± 3 days, respectively. In the present study, both aminoglycosides were well tolerated and there was no patient withdrawal associated with side effect. It is concluded that for intra-abdominal infections, intravenous isepamicin given once daily is as effective as intravenous amikacin given twice daily in combination with metronidazole. (Med J Indones 2001; 10: 88-94)Keywords : Isepamicin, amikacin, inta-abdominal infections